A Detailed Investigation of Electronic and Intersubband Optical Properties of AlxGa1-xAs/Al0.3Ga0.7As Multi-Shell Quantum Dots - Kavruk, Ahmet Emre; Sahin, Mehmet; Atav, Ulfet (IOP Publishing Ltd, 2014)
In this study, we have investigated the electronic and intersubband optical properties of Al x Ga1-x As/Al0.3Ga0.7As/Al y Ga1-y As/Al0.3Ga0.7As multi-shell quantum dot heterostructures as a function of the Al doping concentrations in both the core (x) and the well (y) regions for cases with and without a hydrogenic donor impurity. Our results reveal how resonant absorption wavelengths and absorption coefficient strengths are changed by variation of the Al content in the core (x) and well (y) regions. Besides this, how the electronic and intersubband optical properties of this structure are affected by the existence of the impurity has also been shown. The physical reasons for this relationship between the electronic and optical properties of this structure and the Al content in the core and well regions have been discussed in detail.
Sahin, Mehmet/0000-0002-9419-1711; Atav, Ulfet/0000-0002-2367-6666
Keywords: Multi-Shell Quantum Dot; Intersubband Transition; Oscillator Strength; Absorption Coefficient